2022
DOI: 10.1039/d1tc04618g
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive room-temperature acetone gas sensors employing green-solvent-processed aligned InNdO nanofiber field-effect transistors

Abstract: The development of a high-performance acetone gas sensor for detecting low concentrations of acetone gas is still a key issue. Here, we propose the green-solution-processed electrospinning technique to construct Nd-doped...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…The advantage of this preparation method is that long-distance, high-density as well as uniformly distributed aligned nanofibers can be collected. The common methods for the preparation of metal oxide nanofibers include hydrothermal methods, chemical vapor deposition, template synthesis, and electrospinning processes. Compared with other processes, the electrospinning process has the advantages of low cost, simple operation, and easy large-scale preparation. , In addition, some morphology-controlled nanofibers, such as porous, core–shell structured, aligned, and single-rooted, can be prepared by electrospinning. , The structure of the aligned Gd-doped In 2 O 3 nanofiber FETs prepared by the parallel-plate electrode method is illustrated in Figure b, this bottom-gate-top contact configuration provides the convenience of immobilizing DNA in the active layer, as well as the possibility of realizing applications in biosensing. The SEM images of the unaligned Gd-doped In 2 O 3 nanofibers after annealing at 500 °C for 2 h are observed in Figure c–e, where the arrangement of nanofibers is completely without any directionality.…”
Section: Resultsmentioning
confidence: 99%
“…The advantage of this preparation method is that long-distance, high-density as well as uniformly distributed aligned nanofibers can be collected. The common methods for the preparation of metal oxide nanofibers include hydrothermal methods, chemical vapor deposition, template synthesis, and electrospinning processes. Compared with other processes, the electrospinning process has the advantages of low cost, simple operation, and easy large-scale preparation. , In addition, some morphology-controlled nanofibers, such as porous, core–shell structured, aligned, and single-rooted, can be prepared by electrospinning. , The structure of the aligned Gd-doped In 2 O 3 nanofiber FETs prepared by the parallel-plate electrode method is illustrated in Figure b, this bottom-gate-top contact configuration provides the convenience of immobilizing DNA in the active layer, as well as the possibility of realizing applications in biosensing. The SEM images of the unaligned Gd-doped In 2 O 3 nanofibers after annealing at 500 °C for 2 h are observed in Figure c–e, where the arrangement of nanofibers is completely without any directionality.…”
Section: Resultsmentioning
confidence: 99%
“…This device was investigated using acetone detection at room temperature, and it exhibited excellent properties with an 85% response at 4 ppm, 31 and 53 s response and recovery times, respectively, as well as a 69 ppb detection limit. [112] A nanofiber with an ordered structure is mechanically stable and has well-defined current channels, which limits the likelihood of resistance variations induced by various contact points in the nanofiber network and enhances its sensing performance in comparison to that with a disordered structure. In 2020, Zhang et al fabricated an InYbO nanofiber FET sensor.…”
Section: Inorganic Metal Oxidesmentioning
confidence: 99%
“…Acetone, one of the most toxic and irritating volatile organic gases, can cause coma and vomiting in the human body when it is inhaled at a level above 173 ppm. Moreover, long-term exposure to high-concentration acetone will lead to central nervous system anesthesia and liver damage. , Medical studies have shown that acetone can be a marker of the exhaled gas of diabetes since the concentration of exhaled acetone would be as high as 1.8 ppm for diabetic patients but is well around 300–900 ppb for healthy people. , The accurate detection of acetone concentration is one of the most important auxiliary methods for both medical diagnosis and air quality control. The conventional ways of detecting acetone gas, such as gas chromatography, Raman spectroscopy, and electrochemical methods, have the disadvantages of large instruments, high cost, and inconvenient operation. Nevertheless, metal oxide semiconductor (MOS) sensors based on ZnO, SnO 2 , WO 3 , In 2 O 3 , etc., provide an effective platform with small size, high sensitivity, and easy operation for detecting acetone gas. Hence, designing an acetone analyzer based on MOS nanomaterials with superior selective sensing performances typically at a low concentration under high relative humidity is significantly attractive in the field of sensors.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Medical studies have shown that acetone can be a marker of the exhaled gas of diabetes since the concentration of exhaled acetone would be as high as 1.8 ppm for diabetic patients but is well around 300−900 ppb for healthy people. 3,4 The accurate detection of acetone concentration is one of the most important auxiliary methods for both medical diagnosis and air quality control. The conventional ways of detecting acetone gas, such as gas chromatography, Raman spectroscopy, and electrochemical methods, have the disadvantages of large instruments, high cost, and inconvenient operation.…”
Section: Introductionmentioning
confidence: 99%